Advancements in cyclodextrin-based controlled drug delivery: Insights into pharmacokinetic and pharmacodynamic profiles - Sharif Neaz; Md Mahbub Alam; Abu Bin Imran (Heliyon)
This article discusses and summarizes some fascinating outcomes and applications of cyclodextrins (CDs) and their derivatives in drug delivery. These applications include the administration of protein, peptide medications, and gene delivery. Several innovative drug delivery systems, including NPs, microspheres, microcapsules, and liposomes, are designed with the help of CD, which is highlighted in this article. The use of these compounds as excipients in medicine formulation is reviewed, in addition to their well-known effects on drug solubility and dissolution, as well as their bioavailability, safety, and stability. Furthermore, the article focuses on many factors that influence the development of inclusion complexes, as having this information is necessary to manage these diverse materials effectively. An overview of the commercial availability, regulatory status, and patent status of CDs for pharmaceutical formulation is also presented. Due to the fact that CDs can discover new uses in drug delivery consistently, it is predicted that they will solve a wide range of issues related to the distribution of a variety of unique medications through various delivery channels.